2008
DOI: 10.1093/ndt/gfn431
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gestational age and growth restriction on compensatory kidney growth

Abstract: While in full-term and near-term SGA infants RKL is similar to or even higher than that of AGA infants, in smaller preterm babies (<36 weeks of GA) the RKL is impaired up to the second year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 29 publications
2
20
0
4
Order By: Relevance
“…Hyperfiltration might increase renal mass while glomerular number is relatively low [37]. However, it is not possible to distinguish hypertrophy or normal growth by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperfiltration might increase renal mass while glomerular number is relatively low [37]. However, it is not possible to distinguish hypertrophy or normal growth by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed various postnatal factors including nephrotoxic drugs, undernutrition and stress (infection, oxidative stress) may impair extrauterine nephrogenesis. Ultrasound measurement of kidney size during postnatal growth in humans has shown that even at the age of 8 years, kidney size is lower in children who were born preterm [66,67]. More studies are clearly needed to assess renal postnatal development in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…SGA infants have lower nephron numbers at birth than those born AGA, and SGA and extremely preterm infants may also have lower KL during the first 2 years of life [23,30]. NC might further affect the early renal development in this group.…”
Section: Discussionmentioning
confidence: 99%